Ce/TiOₓ-functionalized catalytic ceramic membrane for hybrid catalytic ozonation-membrane filtration process: fabrication, characterization and performance evaluation - Lee, Wen Jie (2022)
A series of Ce/TiOx-functionalized catalytic ceramic membranes (CeTi-CeCCMs) were fabricated via citrate sol-gel assisted wet impregnation followed by acid-hydrolysed sol-gel dip coating method. The effect of Ce-dopant and block-copolymer P-123 on the formation of Ce-doped TiOx was investigated and optimized to fabricate a uniform Ce-doped TiOx layer with hierarchical porous structure. The modifications adopted for the CCM fabrication had a marginal effect on the clean water permeability, which is favourable towards the membrane filtration process. Meanwhile, the nanocatalysts located at the membrane outer surface and within the membrane substrate of CCM could significantly enhance the accessibility of the reactants to the catalytic sites. The as-fabricated CCMs were employed for N,N-diethyl-m-toluamide (DEET) degradation in the hybrid catalytic ozonation-membrane filtration process operating under continuous dead-end filtration mode. CeTi-CeCCM recorded a high DEET degradation and mineralization with efficient O3(aq) utilization of 1.4 g O3(aq) g−1 TOC removal. The CeTi-CeCCM also exhibited a high antifouling property in the hybrid process by retaining >92% of its initial permeability after 0.5-h operation with humic acid feed. The stability and robustness of the as-fabricated CCM were also tested with multiple filtration-cleaning cycles and using real water feed, respectively. The reactive oxygen species (ROS) quenching and radical detection experiments were conducted to determine the contribution of ROS (i.e. HO[rad], O2[rad]− and 1O2) towards the catalytic activity. The degradation pathways of DEET were proposed and the ecotoxicity of its transformation products (TPs) was estimated. Finally, the mechanistic insights of the O3(aq) decomposition, organic pollutants degradation and mineralization by the CeTi-CeCCM were provided to address the synergistic effect of the membrane filtration and catalytic ozonation occurred in the hybrid process.